Meta‐analysis of the correlation between IL‐6 –174 G/C polymorphism and polycystic ovarian syndrome. Issue 7 (21st March 2015) - Wang, Qiongyao; Tong, Xiaowen; Ji, Yazhong; Li, Huaifang; Lu, Wei; Song, Zhijiao
Abstract Aim The correlation between interleukin‐6 (IL‐6) gene polymorphism and polycystic ovary syndrome (PCOS) has been reported, but the conclusions are controversial. The present study was aimed to evaluate the association between IL‐6 −174 G/C polymorphism and susceptibility of PCOS by meta‐analysis. Material and Methods A systematic search on Medline, Embase, CNKI, Wanfang Data and VIP databases containing Chinese and English studies was conducted electronically using specific eligibility criteria. Meta‐analysis was performed using Review Manager 5.2 software after Hardy–Weinberg equilibrium test. Effect sizes of odds ratio and 95% confidence interval (CI) were calculated and combined appropriately. To verify the reliability of the results, subgroup analyses and sensitivity analyses were performed. Results Four selected studies containing 351 cases and 464 control participants were included. The pooled odds ratio between IL‐6 −174 G/C polymorphism and susceptibility of PCOS under allele (C/G), dominant (CC+GC/GG) and recessive (CC/GG+GC) models were 0.63 (95%CI, 0.41–0.96), 0.53 (95%CI, 0.26–1.08) and 0.67 (95%CI, 0.39–1.16), respectively. The result under allele model was unstable in sensitivity analysis. Subgroup analysis showed that the correlation between IL‐6 –174 G/C polymorphism and susceptibility of PCOS was not statistically significant in the studies that conformed to the Hardy–Weinberg equilibrium. Conclusion IL‐6 –174 G/C polymorphism may be not related to susceptibility of PCOS. Nevertheless, further studies with large samples and studies considering other single‐nucleotide polymorphisms of the IL‐6 gene are needed to confirm our findings.